Analisis Literasi Kimia Peserta Didik di SMAN 1 Batam pada Topik Hukum-Hukum Dasar Kimia dengan Model Rasch - Nyak Mutya Aulina Khairul Fajri; Eka Yusmaita (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
This study aims to analyze the SMAN 1 Batam students’ chemical literacy level on the fundamental chemical laws topic according to the scientific literacy framework adapted by Shwartz. This research is a quantitative study with a sample of 50 XI grade science students from SMAN 1 Batam. Data is obtained from a chemical literacy test on the fundamental chemical laws topic answered by students; the data is analyzed with the Rasch model. The results showed students with the highest ability have a true answer with explanations that unrelated to the text of the items and students with the lowest ability have a wrong or a blank answer. Thus, it was concluded, students with the highest ability have a conceptual scientific literacy level on the hardest item, meanwhile, students with the lowest ability categorized as scientific illiteracy.